De-radicalisation in Indonesia: Discourses and strategies - Tyson, Adam D. (Ministry of Foreign Affairs, Malaysia, 2011)
This article traces the convergence of counter-terrorism strategies and deradicalisation discourses in Indonesia. Key zones of contestation include the classroom with young impressionable pupils, modern society with alienated and dislocated citizens, prison cellblocks with fertile grounds for the spread of radical and pathological ideas, and new media with nearunlimited scope for the diffusion of knowledge. As in any country, Indonesia’s challenge to terror is imperfect and subject to reversals. Counter-terrorism is a means to limit, manage and mitigate terror. Very few claim to be able to eradicate such a threat. Beyond lethal force, there are reflexive, subtle, innovative strategies at the disposal of the Indonesian authorities. Given the constant friction between civil liberties and democratic rights on the one hand, and security imperatives on the other, governing authorities and policymakers are advised to continue consolidating political reforms that began in the transition of May 1998.